Opium-Induced Bowel Dysfunction: A hospital survey in two academic centers of Iran - Daneshbakhsh , Dorsa; Sheikhmiri , Shayan; Hamdieh , Mostafa; Rahimi, Mitra (Student Research in Translational Medicine, 2022)
Background and aim: Opioids abuse is associated with several gastrointestinal side effects. We evaluated the prevalence of gastrointestinal symptoms in OIBD in hospitalized patients in different wards of Shahid Beheshti University of Medical Sciences (SBMU) hospitals. This study aimed to investigate patients' frequency symptoms treated with opioids and opium addicts and their derivatives. Materials and Methods: The present study is a descriptive study conducted from April 2018 to October 2018. Direct interviews with the study population were performed for data collection. Their information, symptoms, and complaints were checked. Results: Among the gastrointestinal symptoms, constipation was the most common symptom (59.3%). This pattern is followed by bloating (28.6%), heartburn (27.1%), abdominal pain (25.7%), dysphagia (22.9%), gastroesophageal reflux disease (22.1%), nausea (12.1%), and vomiting (7.9 %) and diarrhea (5 %) were the next prevalent symptoms, respectively. Conclusion: Finally, our study showed that OBID symptoms are present in most opioid users and most of these people suffer from constipation. Also, the type of substance consumed by the person, the duration of continuous use and cigarette smoking play a role in the incidence of these symptoms.